Exploring Writer Identity in Mexican EFL Students’ Academic Writing - Roux Rodriguez, Ruth; Mora Vazquez, Alberto; Trejo Guzman, Nelly Paulina (Íkala, Revista de Lenguaje y Cultura, 2011)
The objective of this study was to explore writer identity in Mexican undergraduate students of Applied Linguistics writing in English. We focused on the participants' use of first person pronouns and the ways in which they conceptualized their identity as authors of their essays. We employed a combination of text analysis and discourse-based interview methodologies. Findings indicate that participants that made ample use of first person pronouns employed them to present personal experiences rather than to project a strong authorial self. By contrast, those who made little use of first person pronouns seemed to project stronger authorial selves by employing a broader range of stylistic choices. The use of first person pronouns is not essential in the development of strong authorial selves. Higher education should provide better opportunities and resources for students to learn how to project a strong authorial presence in the academic texts they write in English.